In vitro toxicity of metal nanoparticles in two human barrier models: role of the physicochemical features - Pires, J (2022)
Metal nanoparticles (M-NP) are among the most widely used nanomaterials in consumer products available in the market. Thus, human exposure to these nanosized materials is increasing, which raises serious concerns regarding their environmental and human safety. Biological barriers are important lines of defence to xenobiotics, thus expected targets for M-NP. The present study aimed at evaluating the in vitro toxicity of different M-NPs in two cell models of biological barriers: human intestinal (Caco-2) and trophoblastic (BeWo clone b30) epithelial cells. Cells were exposed for 24 h to varied concentrations (0.8-48 µg/cm2) of M-NP of different chemical composition (Au, Ag, TiO2), primary size (10, 30 and 60 nm), capping (citrate, PEG) and crystal structure (rutile, anatase) and toxicity assessed by determining changes in cell morphology, metabolic activity, plasma membrane integrity, generation of intracellular reactive oxygen species (ROS) and intracellular ATP levels. Our data show that the toxicity potential of the tested M-NP is similar in both cell lines with AgNPs > AuNPs > TiO2 NPs, being the effects more visible at higher concentrations. The influence of the size in the cytotoxic-induced effects was more evident for AgNP than for AuNP, with the smaller NP causing more toxicity, being the BeWo cells more sensitive to these M-NP. In addition, PEG-capping effectively attenuated AuNP-induced toxicity in both barrier models. In addition, only cells exposed to AgNP exhibited significant increased levels of ROS. Thus, our data support that the physicochemical properties of M-NP are an important determinant of their cytotoxicity and that intestinal and trophoblastic cells exhibit different sensitivity to the tested M-NP. Future studies would be useful to further explore the effects of M-NP in the human barriers.